Tense-aspect SLA research and Spanish Language Teaching: Is there an influence of research on teaching?. (April 2022) - Comajoan-Colomé, Llorenç
Abstract: This study investigates the relationship between research findings and teaching practice by examining the declared practices and pedagogical content knowledge of teachers in Spanish language teaching (SLT) when teaching the meanings and forms of past tense. Data from an online questionnaire was used to investigate in which order teachers taught three Spanish past forms (preterite, imperfect, and present perfect), their justification for teaching it in a specific order, the main concepts in their pedagogical content knowledge, and whether they thought there was an influence of research in their teaching. A total of 293 teachers of Spanish participated in the study, and results showed that the most common order of teaching past tenses was beginning with the present perfect, followed by the preterite and the imperfect forms, and that the order of teaching was related to the location where Spanish was being taught. The most common justification for teaching in a specific order was the influence of textbooks. Regarding the teachers' pedagogical content knowledge for the teaching of tense-aspect, the most common concepts were related to tense features. Data regarding the influence of research showed that more than half of the participants thought that research was relevant for teaching. Finally, a cluster analysis provided evidence for three distinct profiles of SLT teachers based on their pedagogical content knowledge when teaching tense-aspect.